“Use in Architectural Design” - Daniel Pinson (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This article is the English version of a paper presented 30 years ago, in 1993, for the Laboratoire Architecture, Usage, Altérité (LAUA). The author explores the place historically held by concepts specific to architecture in relation to its societal aims. Highlighting the fact that these concepts have become the poor cousin of architectural theory, Daniel Pinson shows the significance that ‘use’—a modern term covering societal goals that are richer and better understood today thanks to the social sciences—has every right to reclaim in a modern democratic society.